PERAN PROGRAM PEMBINAAN DALAM MENINGKATKAN KESEJAHTERAAN MENTAL NARAPIDANA LANSIA DI LEMBAGA PEMASYARAKATAN - Subroto, Mitro; Alamsyah, Muhammad Faruq (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
This study explores the role of rehabilitation programs in enhancing the mental well-being of elderly inmates in correctional institutions. The urgency of this research stems from the increasing population of elderly prisoners, who often face unique psychological challenges. Utilizing a qualitative approach, interviews and surveys were conducted with both inmates and correctional staff to assess the effectiveness of existing programs. The findings indicate that structured rehabilitation initiatives significantly improve mental health outcomes, fostering a sense of purpose and community among elderly inmates. These results highlight the necessity for continued investment in tailored programs to support this vulnerable demographic within the prison system.Keywords: rehabilitation programs; mental well-being; elderly inmates; correctional institutions; psychological challenges.